P38 The impact of urban renewal on engagement in physical activity in a socio-economically disadvantaged population: a qualitative evaluation. (16th November 2010) - Hunter, R F; Tully, M A; Cleland, C; Cupples, M E; Kee, F; Prior, L; Donnelly, M
Abstract : Background: Most adults in Europe lead sedentary lives; their physical inactivity is associated with a rising prevalence of obesity and is considered to contribute significantly to health inequalities. A recent NICE (2006) review concluded that, "there is an urgent need to conduct research into the effectiveness of environmental interventions, particularly within socially excluded sectors of the population who have the highest prevalence of physical inactivity". Objective: To investigate and utilise the community "knowledge" of individuals living in a socio-economically deprived community and of relevant stakeholders in statutory and voluntary organisations, regarding the design of community-based initiatives on increasing physical activity (PA) levels. Setting: The Connswater Community Greenway is a £32 million investment in East Belfast. The aim of the Greenway is to provide a safe and accessible area which increases PA and improves the people's quality of life. Method: Semi-structured interviews with leading community representatives were conducted regarding (i) the nature and extent to which there are specific groups of residents who would benefit from increased PA, (ii) the nature and provision of PA initiatives, and (iii) practical advice regarding the selection of focus group participants from "Physical Activity Need Groups". Transcriptions were audio recorded and transcribed verbatim. Interim thematic analysis was conducted after each interview to inform the primary questions for subsequent interviews. Findings were validated by a second researcher. Results: Preliminary analysis identified emerging themes relating to the design of successful initiatives. These include the perceived relationship between PA and health, financial and community support, access to facilities, programme content and current service provision. Participants acknowledged that promoting PA has associated health benefits but attributed higher priority to interventions focused on social issues. Short-term funding was a problem for sustaining initiatives and a need for volunteer support was identified. Participants reported local physical and social barriers to community engagement and emphasised the need to involve the local community in planning, to ensure relevance of possible components of interventions to the locality. Perceived needs of particular groups for PA promotion related both to their individual health needs and the geographical area in which they lived. The extent to which groups were perceived as being "hard to reach" influenced the provision of current services. Conclusion: The promotion of PA in a socio-economically deprived area is a complex issue. Results will inform focus group discussions with community representatives and theory-based Intervention Mapping to guide the design of PA initiatives.